The Effect of Karen’s Model in The Achievement and The Development of Levels of Understanding Mathematics for female Students Intermediate - Aziz Kareem, Rafah; Mezaal Mezban, Zuhra (Opción, 2019)
The aim of the research is to identify the effect of the Karen model on the collection and development of understanding levels of mathematics among middle school students.The study sample consisted of (86) female students in the first grade for the second semester of the academic year (2016-2017). The average of Al-Mustaprq for Girls affiliated to the Directorate of Education of Rusafa in Baghdad was chosen as a random choice. (40) in the control group studied according to the usual method. The two groups were rewarded in the following variables: (age in months, previous information, IQ test, achieve- ment score in the first semester, and testing levels of understanding of mathematics).The results of the research tools were: the achievement test which consists of (40) objective paragraphs (multiple choice) and the transition, and testing the levels of understanding of mathematics according to eight levels (primitive knowledge, shape making, form ownership, property observa- tion, (18) Mathematical concepts of each concept Eight paragraphs accor- ding to the levels of understanding were divided into two parts each part (9) concepts. Using the Alpha-Kronbach equation, the stability of the achievement test (0.81) and the stability of the test of comprehension levels (0.86) Two bars. After the experiment was completed, the achievement test was applied and the levels of comprehension (pre-post) were tested on the expe- rimental and control groups.After the data was collected and the test was used for two independent samples and the analysis of the accompanying variance analysis and the quiz test was conducted. As the test of the tribal understanding levels was considered as an associated variable, the results were as follows: There was a statistically significant difference between the experimental and control groups in the achievement test and the testing of the understanding levels in favor of the experimental group. In light of the results of the research, a number of recommendations and suggestions were put forward. The most important of these were the following: Emphasizing the use of the Karen model in teaching mathematical concepts and revealing the levels of understanding possessed by students and developing them through modern models and appropriate means. Sex varia- ble.